Enemigos de Phyllocnistis citrella stainton, encontrados en Malaga - Garrido Vivas, A.=700 1 Del Busto, A.
(Es, En)
ilus., 13 ref.
Keywords: PHYLLOCNISTIS CITRELLA; INSECTA; PARASITOIDES; ESPAÑA; CIROSPILUS; PNIGALIO; SIMPIESIS